Dietary energy density and growing-finishing pig performance and profitability - Young, M.G.; Tokach, Michael D.; DeRouchey, Joel M.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A retrospective analysis of 25 studies (16 at university and 9 at field research facilities) was conducted to model the response in ADG and F/G to increasing dietary energy density and its effect on profitability. Average daily feed intake in the field studies was approximately 30% lower than in the university studies, and as pigs increase in weight in the university studies they transition to a non-energy dependent phase of growth at a lighter weight than those in the field studies. The percentage response in ADG per percent added fat in the university studies was greater for the first 2.5% added fat than for higher fat levels, indicating a diminishing return. However, the percentage response in ADG was similar for both the 2.5 and 5% added fat levels in the field studies, indicating a linear response to fat additions. As expected the F/G improvement was greater in the field compared to the university studies. A five-year price series was used to determine the impact of fat additions to cornsoybean meal-based diets on profitability. For lighter weight pigs (70 to 120 lb), the net return to added fat is almost always positive, with feed cost per unit of gain being increased and deceased 50% of the time. However, the net return to added fat for heavier weight pigs (230 to 265 lb) fluctuates, with feed cost per unit of gain being increased in most scenarios. Using high energy diets for lighter weight pigs is cost effective and increases profit the majority of the time. The optimal energy density for late finishing pig diets is more dependent on the economic conditions.
Keywords: Growing-finishing pigs; Energy density; ADG; Swine